1994
DOI: 10.1089/hwm.1994.11.299
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Treatment and Stabilization of the BTM

Abstract: A technology was developed to treat black tarry materials which contained pentachlorophenol and other hazardous compounds. The technology converted the difficult-to-handle materials to a substance with properties similar to petroleum-based asphalt through heat treatment and polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Farrell and Reinhard 14,15 published complementary papers on the desorption isotherms and desorption kinetics of chlorinated hydrocarbons from model solids and soils. The feasibility of thermally treating black tarry material containing pentachlorophenol and other hazardous compounds was investigated by Hsieh et al 4 Pilot-scale studies with a continuous, indirectly heated rotary kiln desorber were conducted by Fox et al 16 The effects of both the desorber temperature and residence time on the quality of treated soil were investigated. The unit successfully remediated three different types of soil contaminated by PCBs.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Farrell and Reinhard 14,15 published complementary papers on the desorption isotherms and desorption kinetics of chlorinated hydrocarbons from model solids and soils. The feasibility of thermally treating black tarry material containing pentachlorophenol and other hazardous compounds was investigated by Hsieh et al 4 Pilot-scale studies with a continuous, indirectly heated rotary kiln desorber were conducted by Fox et al 16 The effects of both the desorber temperature and residence time on the quality of treated soil were investigated. The unit successfully remediated three different types of soil contaminated by PCBs.…”
Section: Introductionmentioning
confidence: 95%
“…Commercial units have demonstrated that thermal desorption is effective for separating organic compounds from refining wastes and coal tar wastes, creosote from wood treatment wastes, and solvents, pesticides, polychlorinated biphenyls (PCBs), dioxins, and fuel oil from contaminated soils. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations